Dynamics of Telomere Length and Telomerase Activity in the Human Fetal Liver at 5–12 Weeks of Gestation. (2nd July 2018) - Sorochynska, Khrystyna; Sych, Nataliia; Duda, Alla; Kulebyakina, Kateryna; Krasnienkov, Dmytro; Vaiserman, Alexander; Vatlitsov, Denys
Abstract : Fetal stem cell- (FSC-) based therapy is a promising treatment option for many diseases. The differentiation potential of FSCs is greater than that in adult stem cells, and they are more tissue-specific and have lower immunogenicity and better intrinsic homing than embryonic ones. Embryonic stem cells have higher proliferative potential than FSCs but can cause teratomas. Therefore, an evaluation of this potential represents an important biomedical challenge. Since regulation of telomere length (TL) is one mechanism governing cellular proliferation, TL is a useful surrogate marker for cell replicative potential. The prenatal dynamics of TL, however, has never been comprehensively studied. In the present study, dynamics of TL and telomerase activity in the human fetal liver during 5–12 weeks of gestation is examined. Both TL and telomerase activity were positively correlated with week of gestation. For both parameters studied, the trend to increase was evident up to 10th week of gestation. After that, they reached a plateau and remained stable. These findings indicate that telomerase activity remains high during the fetal stage, suggesting high replicative capacity of FSCs and their considerable potential for transplantation therapies. These findings, however, are preliminary only due to small sample size and require further evaluation.